A Marked Increase in Obstetric Hysterectomy for Placenta Accreta - Xiao-Yu Pan; Yu-Ping Wang; Zheng Zheng; Yan Tian; Ying-Ying Hu; Su-Hui Han (Chinese Medical Journal, 2015)
Background: Obstetric hysterectomy (OH) as a lifesaving measure to manage uncontrolled uterine hemorrhage appears to be increasing recently. The objective of this study was to determine the etiology and changing trends of OH and to identify those at particular risk of OH to enhance the early involvement of multidisciplinary intensive care. Methods: A retrospective study was carried out in patients who had OH in China-Japan Friendship Hospital from 2004 to 2014. Maternal characteristics, preoperative evaluation, operative reports, and prenatal outcomes were studied in detail. Results: There were 19 cases of OH among a total of 18,838 deliveries. Comparing the study periods between 2004–2010 and 2011–2014, OH increased from 0.8/1000 (10/12,890) to 1.5/1000 (9/5948). Indications for OH have changed significantly during this study period with uterine atony decreasing from 50.0% (5/10) to 11.1% (1/9) (P < 0.05), and placenta accreta as the indication for OH has increased significantly from 20.0% (2/10) to 77.8% (7/9) (P < 0.05). Ultrasonography and magnetic resonance imaging (MRI) have been used to make an exact antepartum diagnosis of placenta accreta. A multidisciplinary management led to improved outcomes for patients with placenta accreta. Conclusion: As the multiple cesarean delivery rates have risen, there has been a dramatic increase in OH for placenta accreta. An advance antenatal diagnosis of ultrasonography, and MRI, and a multidisciplinary teamwork can maximize patients' safety and outcome.